The phonetic indication in the words of the Qur'anie proverb - Nasser Hassan Abdel Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This research represents a brief phonetic study of some words of the Qur'anic proverb, aiming to reach the fact that the Qur'anic proverb is the effect of using some of the words because of its phonetic qualities and unique characteristics that fit and harmonize with the meaning that the Qur'anie proverbwants to embody, depict and tell about it. In determining the meaning or adding another meaning on its basic significance, and this study relied on clarifying the meaning of the proverb first, then stopping at the connotation of structures and the significance of utterances.DOI /10.54633/2333-021-042-025